[P261] Image quality assessment of filtered dual energy cone beam CT for radiotherapy. (August 2018) - Skaarup, Mikkel; Edmund, Jens M.; Vogelius, Ivan
Abstract : Purpose: Dual energy (DE) computed tomography (CT), combines two scans obtained with different photon energy spectra. It is known from diagnostic CT to reduce metal artefacts. This study investigates the feasibility of developing a DE protocol for cone-beam CT (CBCT) in radiotherapy. Methods: The DE efficacy depends on the ability to separate the energy spectra of the two scans. Therefore, different thickness of copper (Cu) filtration was added to the high energy scan. The DE CBCT scanning protocol consists of two scans at 80 (low) and 140 (high) kV, respectively. Two different DE protocols with 1 and 2 mm added Cu filtration were created. The filtration was done by physically adding Cu plates onto the kV source of the CBCT system. The mAs was adjusted to keep the doses of both DE protocols on the same level as the standard CBCT. The dose was measured using a CTDI phantom. The DE images, I DE, were created in image space from the high, I high, and low, I low, energy images using I DE ( E ) = w ( E ) ∗ I low + ( 1 - w ( E ) ) ∗ I high where w(E) is a weighting factor dependent on the (pseudo) monochromatic energy, E, of the I DE images. Scans of a Catphan phantom were acquired with the DE CBCT protocols as well as a standard CBCT scan at 100 kV. The Cu filtered DE CBCT scans were investigated with respect to soft tissue image quality as the potential benefit of image artefact reduction should not compromise overall image quality or increase radiation dose compared to the standard CBCT. To quantify the image quality, contrast-to-noise (CNR) measurements were done in regions resembling muscle and fat in the phantom. Results: The radiation dose was 100.1% and 101.4% of the standard CBCT dose for the 1 and 2 mm Cu protocols, respectively. The CNR was found to be 1.3 (standard), 1.4 (DE, 1 mm Cu) and 1.3 (DE, 2 mm Cu). Conclusions: The filtered DE and standard CBCT protocols showed similar performance in radiation dose and soft tissue image quality. Hence it is feasible to explore the potential benefits of increased soft tissue contrast and artefact reduction for DE CBCT protocols.